Midwifery Care Management for Pregnant Women in Mrs. “R” Gestation 20-22 Weeks With Mild Anemia At Mamajang Health Center, June 07- august 2, 2024 - Yayu, Sriwahyuni; Firdayanti, Firdayanti; Taherong, Ferawati; Diarfah , Andi Dian; Andryani, Zelna Yuni (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2026)
Introduction Mild anemia in pregnant women with Hb ≥11 Gr/dl The impact of mild anemia can be moderate to severe anemia in pregnancy, can be fatal if not immediately addressed such as causing miscarriage, premature labor, uterine inertia, prolonged labor, uterine atony, and bleeding and shock. The World Health Organization (WHO) states that globally the prevalence of pregnant women who experience anemia is 83.2% while in Southeast Asia the prevalence is 97.8%. This shows that the prevalence of anemia in Southeast Asia exceeds the global prevalence value. From the data above, it indicates that anemia in pregnant women is one of the important risk factors in health. Research Methods This study aims to implement midwifery care for pregnant women in Mrs.